Materials and Structures - Plizzari, Giovanni; De Belie, Nele.; Provis, John.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Materials and Structures, the flag-ship publication of RILEM, provides a unique international and interdisciplinary forum for new and unpublished research on the performance of construction materials. Among the leaders in its field, the Journal is dedicated to the publication of high-quality papers on the fundamental properties of building materials, their characterization and processing techniques, modeling, standardization of test methods, and the application of research results in building and civil engineering. Always at the leading edge of research, Materials and Structures also publishes comprehensive reports prepared by the technical committees of RILEM.
Keywords: Mechanics; Mechanics, Applied; Civil engineering; Building materials; Materials science; Solid Mechanics; Materials Science, general; Theoretical and Applied Mechanics; Manufacturing, Machines, Tools, Processes; Civil Engineering; Building Materials